Pemberdayaan Masyarakat dalam Mengembangkan UMKM Melalui Digitalisasi di Kelurahan Benowo Kecamatan Pakal Kota Surabaya - Gideon Setyo Budiwitjaksono; Rosanti Amalia Putri; , Nabila Carissa Anindiyadewi; A’isy Sufyaan Alim Pamuji; Nuria Puspita Anggrainy (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Community Service which is integrated with the Independent Thematic Real Work Lecture Merdeka Learning Campus (KKNT MBKM) which was held in Benowo Village, Pakal District, Surabaya City is one of the community empowerment efforts that focuses on home-based businesses (UKM) through mentoring and creative economic training for the community. local. The purpose of the KKNT is to implement the knowledge that students gain in college to help village development and contribute ideas for solutions to social issues. The problems in Benowo Village are the number of SMEs who are not aware of the importance of business branding and business strategy, the lack of optimal use of information technology, and limited knowledge related to digitalization. The method used in community empowerment in Benowo Village is a participatory approach, which includes three stages, namely the preparation stage, the implementation stage, and the evaluation stage. The program carried out is to help empower MSME owners in Benowo Village through business rebranding assistance programs, business training and online marketing, as well as digital content management assistance. MSMEs that are incorporated include small and home-based industries, including: making baked brownies, opat flops, nuggets and sambal pecel, and making pastries. After the implementation of this program, it is hoped that partner MSMEs can continue to develop and follow the development of digitalization so that later they can improve the economic level of the surrounding residents.